Hedonic Test Of Chicken Dumpling(Tum Ayam) With Addition Of Stone Banana Peel (Musa Brachyarpa) As A Healty Food Alternative - Josi, Noviolita Elvina; Ekayani, Ida Ayu Putu Hemy; Damiati, Damiati (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to determine the level of consumer acceptance of chicken tum with the addition of banana stone peel (Musa brachyarpa) as an alternative healthy food. Banana stone peel is a food waste that has not been optimally utilized, despite containing fiber, protein, minerals, and bioactive compounds that can enhance the nutritional value of food products. This research employed an experimental design conducted through three formulation trials to obtain the optimal recipe. A hedonic sensory test involving 50 untrained panelists was performed using a 5-point scale assessing aroma, texture, and taste. The results showed that chicken tum with added banana stone peel was well accepted with a percentage of 50% chicken meat and 50% banana peel, with average scores of aroma 4.70 (highly liked), texture 4.56 (liked to highly liked), and taste 4.56 (liked to highly liked). Based on the hedonic scale conversion, the product falls into the “liked” to “highly liked” category. Therefore, incorporating banana stone peel into chicken tum can serve as a healthy alternative formulation that is nutritious and acceptable to consumers.